Application of the Demonstration Method in Islamic Religious Education Learning in Improving Student Learning Outcomes - Mansyuarna, Mansyuarna; Silajdžić, Adnan; Hamzah, Mohd Shafiee (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to find out whether there is an increase in student learning outcomes in Islamic Religious Education subjects by implementing the Demonstration Method in class VIII in junior high school. Methodology: This research uses a classroom action research approach with two cycles. Each cycle consists of four stages, namely planning, implementation/action, observation, and reflection. The subjects of this research were 28 students in class VIII of junior high school. Data is collected through observation, tests and documentation. Data analysis was carried out using qualitative analysis techniques through the Milles and Huberman interactive model in three stages: data reduction, data presentation, and conclusion/verification, as well as quantitative analysis techniques with descriptive statistics. Main Findings: The research results show that the application of the Demonstration Method significantly improves student learning outcomes in Islamic religious education subjects. At the pre-cycle stage, the percentage of student learning outcomes was 71%. After applying the Demonstration Method, learning outcomes increased to 78% in cycle I. A significant increase occurred in cycle II, where student learning outcomes reached a percentage of 88%. These results indicate that the Demonstration Method is effective in improving students' understanding and learning outcomes in Islamic religious education subjects. Novelty/Originality of this study: This research contributes to the development of learning methods with a focus on the Demonstration Method in the context of Islamic Religious Education learning. The findings of this research provide empirical evidence that the Demonstration Method can help improve student learning outcomes. The results of this research can be used as a reference for educators, researchers and educational practitioners in designing more effective and interactive learning strategies in facilitating students' understanding of lesson material.